GOVERNMENT SPENDING ON TOURISM APPROACHED THROUGH THE PRISM OF CONSOLIDATING THE RIGHT TO REST AND LEISURE - SECRIERU, Angela (Economy and Sociology, 2021)
Every person’s right to rest and leisure, including reasonable limitation of working hours and periodic holidays with pay, as well as the right to freedom of movement without restriction, except as provided by law, determine the opportunity and necessity of the harmonious development of domestic and international tourism. The harmonious development of domestic and international tourism depends on the quality of public policies designed to stimulate the growth of this sector, especially the public expenditure policy. This paper aims to analyse the impact of tourism regarding the respect for the right to rest, the effectiveness of public policies applied in the field of tourism, especially the public expenditure policy aimed to stimulate tourism, to formulate solutions for the development of the tourism sector in the Republic of Moldova by strengthening the right to rest. The Human Development Index (HDI) is considered an aggregated indicator with the capacity to more or less consistently quantify the level of respect for economic, social and cultural rights. Based on the simple regression method, the relationship between HDI as a dependent variable and Travel and Tourism Sector Competitiveness Index (TTCI) as an independent variable is tested. The presented analysis suggests the conclusion that the quality of respect for the right to rest, materialized, including through tourism, is a factor with a major positive impact on the HDI. An important place in the paper is occupied by the generalization of the EU countries experience in the field of public policies designed to stimulate tourism development approached through the prism of respecting the right to rest and leisure.